2008
DOI: 10.1139/t08-064
|View full text |Cite
|
Sign up to set email alerts
|

On equivalent granular void ratio and steady state behaviour of loose sand with fines

Abstract: Abstract:Void ratio has traditionally, been used as a state variable for predicting the liquefaction behaviour of soils under the Critical State Soil Mechanics framework. Recent publications show that void ratio may not be a good parameter for characterizing sand with fines. An alternative state variable referred to as equivalent granular void ratio has been proposed to resolve this problem. To calculate this alternative state variable, a bparameter is needed. This b-parameter represents the fraction of fines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(86 citation statements)
references
References 31 publications
4
77
0
5
Order By: Relevance
“…According to the grain size distribution of MLS and an assumed fthre of 30z, b=0.164 and 0.577 for fc=15 and 30z, respectively, following the method by Rahman et al (2008). However, a b value of 0.65 was required for the case of fc=15z to establish a more consistent e * -CRR correlation, for the combined data of fc=0, 15 and 30z.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the grain size distribution of MLS and an assumed fthre of 30z, b=0.164 and 0.577 for fc=15 and 30z, respectively, following the method by Rahman et al (2008). However, a b value of 0.65 was required for the case of fc=15z to establish a more consistent e * -CRR correlation, for the combined data of fc=0, 15 and 30z.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, natural or artiˆcially mixed M/S soils may not meet the description of binary packing in a strict sense and the thresholdˆnes content may therefore not be 30z. Some of the studies on artiˆcial silty sand specimens, mostly silica in nature, have demonstrated that the thresholdˆnes content generally ranged from 25 to 45z (Koester, 1994;Polito, 1999;Xenaki and Athanasopoulos, 2003;Papadopoulou and Tika, 2008;Rahman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the concept appears to be attractive, the physical meaning of index b in the equivalent skeleton void ratio is not yet well understood. In the literature the parameter b is commonly assumed to be a constant that can be back analyzed from test data or predicted by some empirical expression [4][5][6]. In the writers' view, the parameter b should vary during the shearing process; in other words it is a state dependent variable.…”
Section: Introductionmentioning
confidence: 99%